The police and violence - Sherman, Lawrence W. (The Annals of the American Academy of Political and Social Science ;0002-7162, 1980)
Articles in this volume discuss efforts by the police to reduce violence in society and the problem of the use of violence by and against the police. The introductory article notes that when police attempt to stop violence, they must often be violent themselves. One paper demonstrates the personal and institutional consequences of the moral dilemmas involved in police work; when police use 'dirty' means to achieve good ends they may lose their sense of moral proportion. Empirical evidence of violence against police is presented. For example, the first systematic analysis of the circumstances surrounding police killings is discussed, and the myth that many officers are killed in family fights is deflated. The practice of arming off-duty police officers is criticized by another contributor as harmful to both police officers and citizens. Ways in which police behavior might be changed to reduce injuries to citizens are suggested in two papers which show how prior decisions can constrain the options an officer has by the time a confrontation develops. Also discussed are police shootings at minorities in Los Angeles. Many contributors point to the need for more research, especially concerning violence against the police. Scarcity of basic data accounts for lack of practical solutions to the problems of violence and police. Footnotes, case studies, and statistical data are included